Cathode materials in non-aqueous aluminum-ion batteries: Progress and challenges. Issue 17 (1st December 2020) - Zhou, Qiuping; Zheng, Yujing; Wang, Dawei; Lian, Yue; Ban, Chaolei; Zhao, Jing; Zhang, Huaihao
Abstract: Aluminum-ion batteries (AIBs) are considered as alternatives to lithium-ion batteries (LIBs) due to their low cost, good safety and high capacity. Based on aqueous and non-aqueous AIBs, this review focuses on the research progress of the latter cathode materials. Firstly, we fully explain the aluminum storage mechanism of different types of materials. Next, according to relative statistical data, the research trend of different cathode materials (transition metal chalcogenides, transition metal oxides and carbon-based materials) in non-aqueous AIBs is summarized, and related electrochemical performance are analyzed and compared in detail. In addition, as for the research of non-aqueous AIBs cathode materials, the existing problems and expected solutions are discussed, as well as the proposed future research directions.